Metabolomics Integrated with HPLC-MS Reveals the Crucial Antioxidant Compounds of Muscadine Wine - Fei Xue; Bohan Yang; Peining Fu; Yachun Peng; Jiang Lu (MDPI AG, 2022)
Wine is a kind of beverage with a variety of compounds beneficial to human health, which makes it popular all over the world and it contributes importantly to economics. The excessive oxidation of wine has always been a major problem in wine production and storage. Unlike traditional wines which are made from Eurasian grapes, wines made from muscadine grapes (Muscadinia rotundifolia Michx.) can maintain their sensory qualities under natural oxidation conditions for relatively long periods of time despite the insight mechanisms still being unclear. In this study, two muscadine wines, Carlos (CAL) and Noble (NOB), and two traditional wines, Chardonnay (CH) and Marselan (MAS), were chosen for comparison of their compositional alteration during oxidation, in order to analyze the principal components contributing to the antioxidant characteristics of muscadine wines. The DPPH, ORAC, color intensity, and total phenolic content changes during the natural oxidation process were analyzed. Six core significantly changed metabolites (SCMs, avicularin, beta-lactose, delphinidin-3-O-glucoside, ellagic acid, myricetin, and 4-methylcatechol [p < 0.05]) related to the oxidation process were determined. In addition, HPLC-MS was also used to identify pyrogallol which is a unique antioxidant compound in muscadine wine. The present work aims to reveal the crucial antioxidant compounds of muscadine wine and provide valuable information and a new platform for future research on wine oxidation.